(untitled) (Research, Society and Development, 2024)
Introduction: Telemedicine has emerged as a crucial tool in the management of chronic diseases, offering innovative solutions to improve access and quality of healthcare. Defined by the World Health Organization (WHO) as the provision of healthcare services at a distance using information and communication technologies, telemedicine has shown efficacy in early detection, prognosis, and monitoring of chronic disease progression. Objective: This article aims to provide a comprehensive overview of the role of telemedicine in the management of chronic diseases, highlighting technological advances, challenges faced, and clinical implications to improve patient outcomes. The methodology includes an integrative literature review, using databases such as PubMed, Scopus, and Web of Science to identify relevant studies. Search terms included "telemedicine," "chronic diseases," and "health management." Results: The use of telemedicine demonstrates potential to improve glycemic control in diabetics, reduce blood pressure in hypertensive patients, and manage exacerbations in patients with COPD. However, the heterogeneity of results, clinical validation, and complexity of data interpretation remain significant challenges. Discussion: Telemedicine offers significant economic advantages and improves access to healthcare. However, the lack of adequate technological infrastructure and issues of data privacy and security are barriers to its adoption. Conclusion: Telemedicine is an effective and economical tool for the management of chronic diseases, but overcoming technological challenges and integrating with existing healthcare systems are crucial to maximizing its benefits.